The Relationship Between Peer Interaction and Speaking Skills of Fourth-Grade Students at SD Inpres 5/81 Mallari, Bone Regency - Satriani, Satriani; Rosmalah, Rosmalah; Waliyyu, Aqilah Al (International Journal of Elementary School Teacher, 2025)
This research is motivated by peer interaction and students' speaking skills. This research is a type of correlational research with a quantitative approach that aims to determine whether or not there is a significant relationship between peer interaction and speaking skills of fourth grade students of SD Inpres 5/81 Mallari, Bone Regency. The population in this study were 20 fourth grade students using a saturated sample technique. Peer interaction data were collected through a questionnaire instrument and student speaking skills data were collected through a test. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, it was obtained that peer interaction was in the high category with an average of 65.63% and students' speaking skills with an average of 55.76% in the moderate category. The results of the inferential statistical analysis showed that there was a significant relationship between peer interaction and students' speaking skills with a correlation coefficient of 0.545 and was in the moderate category. Thus, H0 was rejected and H1 was accepted. So it can be concluded that there is a significant positive relationship between peer interaction and speaking skills of fourth grade students of SD Inpres 5/81 Mallari, Bone Regency